2005
DOI: 10.1145/1089023.1089026
|View full text |Cite
|
Sign up to set email alerts
|

On the impossibility of dimension reduction in l 1

Abstract: The Johnson-Lindenstrauss lemma shows that any n points in Euclidean space (i.e., R n with distances measured under the 2 norm) may be mapped down to O((log n)/ε 2 ) dimensions such that no pairwise distance is distorted by more than a (1 + ε) factor. Determining whether such dimension reduction is possible in 1 has been an intriguing open question. We show strong lower bounds for general dimension reduction in 1 . We give an explicit family of n points in 1 such that any embedding with constant distortion D r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
152
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(156 citation statements)
references
References 27 publications
4
152
0
Order By: Relevance
“…A major reason that dimension plays only a minor role when we consider embeddings into l 2 is the following theorem which shows that in l 2 the dimension can be significantly reduced without significant loss in distortion. (We note that the analogous statement for l 1 does not hold; see [BC03,LN04].) Theorem 13.3 (Johnson-Lindenstrauss [JL84]).…”
Section: Metric Embeddingmentioning
confidence: 95%
“…A major reason that dimension plays only a minor role when we consider embeddings into l 2 is the following theorem which shows that in l 2 the dimension can be significantly reduced without significant loss in distortion. (We note that the analogous statement for l 1 does not hold; see [BC03,LN04].) Theorem 13.3 (Johnson-Lindenstrauss [JL84]).…”
Section: Metric Embeddingmentioning
confidence: 95%
“…It has been shown that a stronger guarantee, such as preserving distances to within a 1 ± ǫ factor with high probability, as given by Johnson-Lindenstrauss, does not exist for ℓ 1 distance. 38 To the best of our knowledge, the NN matching performance for quantized versions of these embeddings has not yet been reported.…”
Section: Extension To Nn Search Based On Non-euclidean Distance Measuresmentioning
confidence: 99%
“…How about l1 as target metric? Then the situation is even worse, as Brinkman and Charikar [11] proves that for every n, the embedding of an n-point l1 metric into 1 Regarding l  as the target metric, Matousek [12] showed that any n-point metric can be embedded into d l  With distortion c and of dimension Furthermore, an almost matching lower bound can be proved, so the target dimension cannot remain bounded for a general…”
Section: mentioning
confidence: 99%